Electrochemical Oxidation of Niobium and Tantalum Carbides in Aqueous Solutions. (7th July 2017) - Walczyk, Dustin J.; Mason, Daniel; Palazzo, Benjamin G.; Norris, Zach; McRae, Naquan; Tran, A. T.; Hettinger, Jeffrey; Yu, Lei
Abstract : Transition metal carbides have unique properties such as high hardness, high melting point, high thermal conductivity, and high chemical stability. At a temperature of 350 o C or higher, some metal carbides can react with chlorine gas to form volatile metal chlorides. At room temperature, metal carbides are very stable in several strong acid solutions. However, metal carbides can be oxidized electrochemically. Then, metal oxides can be produced and dissolved in the solutions. In this report, we investigate the electrochemical properties of a series of metal carbides including NbC, Nb2 C, TaC, and Ta2 C in aqueous solutions with the presence of HCl and HF. Cyclic voltammetry and elemental analysis demonstrated that all of these metal carbides can be oxidized electrochemically at a "mild" electrode potential and produce soluble metal ions in the solutions.